2011
DOI: 10.19030/iber.v3i4.3685
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Exchange Rates On International Transfer Pricing Decisions

Abstract: The following Table was submitted by the authors as an update, however, the International Business & Economics Research Journal, Volume 3, Number 3, page 39 had already gone to press. We apologize for any inconvenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
8
0
4
Order By: Relevance
“…But not in accordance with research conducted by Chan, Landry, and Jalbert (2004) and Bernard et al, (2006). According to Chan, Landry, and Jalbert (2004) states that multinational companies may try to curb foreign exchange rate risk by moving funds into strong currencies through transfer pricing to maximize overall corporate profits.…”
Section: E the Effect Of Exchange Rate On Transfer Pricingmentioning
confidence: 97%
See 1 more Smart Citation
“…But not in accordance with research conducted by Chan, Landry, and Jalbert (2004) and Bernard et al, (2006). According to Chan, Landry, and Jalbert (2004) states that multinational companies may try to curb foreign exchange rate risk by moving funds into strong currencies through transfer pricing to maximize overall corporate profits.…”
Section: E the Effect Of Exchange Rate On Transfer Pricingmentioning
confidence: 97%
“…Transfer pricing can be used to reduce the exposure of multinational corporations' transactions on the risk of exchange rate changes by moving funds into strong currencies. According to Chan, Landry, and Jalbert (2004) states that multinational companies may try to curb foreign exchange rate risk by moving funds into strong currencies through transfer pricing to maximize overall corporate profits. Bernard et al, (2006) also found that there is an effect of exchange rate on transfer pricing decisions inside and outside the firm; an appreciation of the dollar reduces the difference between the prices.…”
Section: Introductionmentioning
confidence: 99%
“…Different results are delivered by Qiansyah (2016) and Putri et al (2018) that tax minimization has no effect on transfer pricing. Research results by Chan et. al.…”
Section: Introductionmentioning
confidence: 93%
“…This research is in accordance with agency theory, Jensen & Meckling (1976) explained that there is an assumption of human nature that underlies agency theory, which is selfish and tends to dislike risk. Correspondingly, the companies are faced with the economic risk of exchange rate, so they will try to reduce the exchange rate risk by moving funds to a strong currency through transfer pricing (Chan et al, 2004). Cravens & Shearon (1996) stated to control the risk of gains and losses from foreign currency transactions, the companies will use transfer pricing as a protective fence to deal with changes in exchange rates.…”
Section: The Effect Of Exchange Rate On Transfer Pricingmentioning
confidence: 99%
See 1 more Smart Citation